Time-restricted eating on inflammation and oxidative stress in overweight, older adults - Ezzati, Armin (Kansas State University, 2024)
The aim of this dissertation was to provide innovative insights into the effects of various dietary interventions on inflammation, oxidative stress, and metabolic health. Chapter 1 presents a comprehensive review discussing the rationale for assessing inflammation and oxidative stress in the context of time-restricted eating (TRE). This review suggests the potential effects of TRE on pro-inflammatory cytokines, including tumor necrosis factor-alpha (TNF-α), interleukin-1β (IL-1β), IL-6, IL-8, and IL-10, as well as oxidative stress related to Alzheimer's disease in humans. Chapter 2 reviews the importance of different types of intermittent fasting (IF) regimens, including alternate-day fasting, the 5:2 diet, time-restricted eating, and Ramadan fasting, in mitigating inflammation and lowering oxidative stress. It highlights the potential of IF regimens in attenuating inflammatory responses. Chapter 3 presents a systematic review comparing the effects of isocaloric IF versus daily caloric restriction (DCR) on weight loss and metabolic risk factors for chronic noncommunicable diseases in adults with overweight and obesity. This review synthesized findings from randomized controlled trials and found that the effects of IF regimens on plasma lipid, glucose, insulin levels, HbA1c, and inflammatory markers were highly variable but generally comparable with DCR. IF (4:3 and 5:2 diets) was superior to DCR for improving insulin sensitivity in two studies. Reductions in body fat were significantly greater with IF (5:2 diet and TRE) than with DCR in two studies. Given the limited number of long-term studies using isocaloric or eucaloric IF interventions compared with control groups, future studies should incorporate more rigorous controls across intervention arms, as well as controls for energy intake and balance, nutrient composition, and weight loss. In Chapter 4, we conducted another systematic review on whether TRE confers additional benefits through mechanisms beyond calorie restriction (CR) alone or whether the benefits of TRE are related to unintentional reductions in calorie intake. The reviewed outcomes included anthropometric and metabolic outcomes (lipid levels, fasting blood glucose, HOMA-IR, and blood pressure). A novel finding of this review was that longer daily fasting periods (≥16 hours), combined with moderate CR, resulted in significant improvements in measures of insulin resistance (HOMA-IR) in five out of six studies where it was assessed. In contrast, CR alone did not improve this marker in short- or mid-term interventions (8 to 52 weeks) without a specific dietary intervention (e.g., Mediterranean diet). Greater weight loss and reductions in diastolic blood pressure were noted with CR + TRE compared with CR alone after 8 to 14 weeks, whereas one study reported greater improvements in triglycerides and glucose tolerance with CR + TRE (3 days/week) compared with CR alone following 26 weeks. Other metabolic outcomes did not significantly differ between the two interventions. Chapter 5 presents a secondary analysis of a pilot study investigating the effects of TRE on inflammation (TNF-alpha, IL-1beta, IL-6, high-sensitivity C-reactive protein) and oxidative stress (8-isoprostane) in older adults with overweight. No significant differences were found in the outcomes of interest compared to baseline after four-week TRE (16:8) intervention. A short-term TRE intervention produced reductions in TNF-α [43.2 (11.2) pg/ml to 39.7 (10.0) pg/ml (p = 0.101)] with a Cohen's d effect size of 0.33 and IL-1β levels [1.4 (0.8) pg/ml to 1.3 (0.6) pg/ml (p = 0.499)] with a Cohen's d effect size of 0.23, indicating potential anti-inflammatory benefits. Consistent with previous studies, IL-6 and hs-CRP levels showed no significant changes. Oxidative stress marker 8-isoprostane levels decreased slightly from 39117.6 (12787.5) pg/ml to 38694.7 (11631.4) pg/ml (p = 0.919), with a Cohen's d effect size of 0.07. Collectively, these findings provide initial insights into the potential effects of TRE on inflammatory and oxidative stress markers in older adults. Well-powered larger trials with longer durations are warranted to elucidate the potential of TRE in aging populations.
Keywords: Time-restricted eating; Inflammation; Oxidative stress; Intermittent fasting; Older adults